Study of the performance of five parameter model for monocrystalline silicon photovoltaic module using a reference data - Hashim Emad Talib (FME Transactions, 2018)
This paper presents the construction of a model for a photovoltaic module using the single-diode five-parameter model, based exclusively on datasheet parameters. The model takes into account the series and parallel (shunt) resistance of the module. This easy and accurate method of modeling photovoltaic module, which is able to predict the module behavior in different temperatures and irradiance conditions under climate conditions of Baghdad city, is built and tested. This paper indicates how the parameters of the five-parameter model are determined, also estimates the output power generated and other electrical and internal parameters by photovoltaic module and compares predicted current-voltage curves and power-voltage curves with experimental data for monocrystalline and for four months. The theoretical results showed a slight increase in shunt resistance and photocurrent with solar radiation increasing. Also, the paper evaluates effects of weather factors on cell temperature using a simple formula. The results show that there is difference between theoretical (modeled) and experimental results. The maximum power validation result at radiation of 500, 750 and 1000W/m2 was 5.5% in January, 18.4% in April and 20% in April respectively, the best validation of maximum power under standard testing conditions (STC) was 14.8% in January. The results obtained from modeling show agreement with experimental results of module temperature.